OFET based H2S gas sensing among reducing and mining gases using green synthesis SnO2 - Surya, S. G.; Roy, S.; Ganne, B. S. P.; Pasam, D.; Sastry, A. B.; Bhagavatula L. V. Prasad (2016 3rd International Conference on Emerging Electronics, ICEE 2016, 2017)
In this paper we present detection of H2S gas using an organic field effect transistor (OFET) based sensor. A low-cost green synthesis process for SnO2 nanoparticles and bi-layer approach for device fabrication have been adopted to come up with the sensor. With the help of multiparameteric analysis, selectivity towards H2S gas was proved among other reducing and mining gases.